URGENCY OF LEGAL CONSEQUENCES TO THE ABSENCE OF PROVISIONS FOR THE PERIOD OF IMPLEMENTATION OF DEPORTATIONS IN IMMIGRATION LAW - asto yudho kartiko; Muhammad Azzam Alfarizi (Journal of Law and Border Protection, 2021)
Deportation is an act of expelling foreigners who violate the law in order to maintain the sovereignty of the country. however, article 85 of Law Number 6 of 2011 concerning Immigration is not regulated regarding the period of deportation. This is by the National Legal Development Agency of the Ministry of Law and Human Rights of the Republic of Indonesia in the Final Report on the Evaluation of Immigration Law in 2020. The formulation of the problem of this study is how the legal consequences are on the absence of provisions governing the period of deportation. The research method used is a qualitative-normative metde with a conceptual approach. The results of this study are due to the law, namely the occurrence of overcapacity, there are detainees who have served more than 10 years of detention, and the occurrence of conflicts of detention with officers and between detainees. The advice that can be given is to immediately make provisions for the period of implementation of deportation.